Thyroid hormone use during cardiac transplant organ procurement - Cooper, Lauren B.; Milano, Carmelo A.; Williams, Melissa; Swafford, Wendy; Croezen, Donna; Van Bakel, Adrian B.; Rogers, Joseph G.; Patel, Chetan B. (Clinical transplantation, 2016)
Background Acute hypothyroidism after brain death results in hemodynamic impairments that limit availability of donor hearts. Thyroid hormone infusions can halt that process and lead to increased utilization of donor organs, but prolonged use of thyroid replacement has not been well studied. Methods We developed a 15‐question survey regarding policies, procedures, and reporting of thyroid hormone use by organ procurement organizations (OPOs). The survey was posted for 5 weeks on the Association of OPOs Portal. Results We received 29 responses, representing 24 OPOs. Seventy‐two percent reported their OPOs use thyroid hormone for all potential donors and 90% have a protocol for thyroid hormone use. There is a large variation in the maximum dose of thyroid hormone used, and many OPOs have no weaning protocol. Most OPOs do not collect data on total thyroid hormone administered during procurement and would favor more detailed report of thyroid hormone use. Conclusions Thyroid hormone use can have important implications for organ selection and cardiac function before and after transplantation. Protocols vary widely with respect to why and how to use and wean thyroid hormone. We believe there should be more detailed reporting of thyroid hormone use for future studies to ensure appropriate donor management.